The Influence of Emotional Intelligence and Job Burnout on The Turnover Intention Employee’s at PT Banjarmasin Bangkit - Ulyani, Farida; M. Hasanur Arifin; Rizky Muslim Hidayat; Humaidi (Journal of Business Transformation and Strategy, 2024)
Abstract: This research aims to investigate the effect of emotional intelligence and job burnout on the turnover intention. This study uses a quantitative analysis method which aims to analyze the relationship between the observed variables using multiple regression analysis. Respondent consists of 46 employees of PT. Banjarmasin Bangkit taken with a saturated sample technique. The data collection method used a questionnaire and analyzed using SPSS 26. The results of the research proves that emotional intelligence has a positive and significant affect partially on the turnover intention with the influence of 0,637 or 63,7% and job burnout has a positive and significant affect partially on the turnover intention with the influence of 0,274 or 27,4%. Emotional intelligence and job burnout have significant effect simultaneously on the turnover intention with the influence of 0,753 or 75,3%.   Keywords: Procedures Emotional Intelligence, Job Burnout, Turnover Intention